Dual mobility in primary total hip arthroplasty: current concepts. Issue 11 (8th November 2019) - Cuthbert, Rory; Wong, James; Mitchell, Philip; Kumar Jaiswal, Parag
Abstract : Total hip arthroplasty (THA) is one of the most successful surgical procedures – reducing pain and providing functional improvement. However, THA instability is a disabling condition and remains the most common indication for revision THA. To combat the risk of instability, the concept of dual mobility (DM) was developed. This article provides a comprehensive review of DM in the literature. Widespread use of first-generation DM was limited due to concern regarding wear of the polyethylene head and the unique complication of intraprosthetic dislocation (IPD). Implant modifications using highly cross-linked, durable polyethylene and a smooth, cylindrical femoral neck have all but eliminated IPD in contemporary DM. In multiple studies, DM demonstrates statistically significant reductions in dislocation rates comparative to standard bearing primary THA. These results have been particular promising in high-risk patient populations and femoral neck fractures – where low dislocation rates and improved functional outcomes are a recurrent theme. From an economic perspective, DM is equally exciting – with lower accrued costs and higher accrued utility comparative to standard bearing THA. Longer-term clinical evidence and higher-quality prospective comparative studies are required to strengthen current research. Dual mobility may well represent the future gold standard for THA in high-risk patient populations and femoral neck fractures, but due diligence of long-term performance is needed before recommendations for widespread use can be justified. Cite this article: EFORT Open Rev 2019;4:640-646. DOI: 10.1302/2058-5241.4.180089